Hubungan Motivasi Belajar terhadap Kemampuan Membaca Siswa di SDN 5 Kabila Bone - Sulastya Ningsih; Mia Nur Ara; Sri Cindi Patuti; Dewi Fitriani; Adelia Putri Abas; Deliyawati Hairi; Elvian Bakari (Sekolah Tinggi Agama Islam Yayasan Pendidikan Ilmu Qur'an Baubau, 2026)
This study aimed to determine the effect of learning motivation on students' reading ability at SDN 5 Kabila Bone. The research employed a quantitative approach with a correlational design. The participants consisted of 30 first- and second-grade students selected through total sampling. Data were collected through learning motivation questionnaires, reading ability tests, and classroom observations conducted during the learning process. The results showed that the majority of students had a high level of learning motivation (60%), while 50% demonstrated good reading ability. Statistical analysis revealed a strong positive relationship between learning motivation and reading ability, with a Pearson correlation coefficient of 0.72. Furthermore, the coefficient of determination (R²) of 0.52 indicated that learning motivation contributed 52% to students' reading ability, while the remaining 48% was influenced by other factors, such as parental support and the quality of the learning environment. Students with higher learning motivation tended to read more fluently, comprehend reading materials better, and demonstrate greater confidence during learning activities. The hypothesis testing also confirmed that the relationship was statistically significant at the 0.05 significance level. Therefore, it can be concluded that learning motivation has a positive and significant effect on students' reading ability at SDN 5 Kabila Bone. These findings highlight the importance of collaboration among teachers, parents, and schools in fostering students' learning motivation to enhance their reading skills effectively.